In Vivo Pharmacodynamics of Calophyllum soulattri as Antiobesity with In Silico Molecular Docking and ADME/Pharmacokinetic Prediction Studies - Inarah Fajriaty; Hariyanto Ih; Irda Fidrianny; Neng Fisheri Kurniati; Muhammad Andre Reynaldi; I Ketut Adnyana; Rommy Rommy; Fransiska Kurniawan; Daryono Hadi Tjahjono (MDPI AG, 2023)
This study aims to determine the antiobesity activity of Calophyllum soulattri leaves extract (CSLE) on high fat diet-fed rats (HFD) and to predict the molecular docking and pharmacokinetics of selected compounds of Calophyllum soulattri to fat mass and obesity-associated protein (FTO). Daily body weight, organ, carcass fat (renal and anal), body mass index, total cholesterol, and total triglyceride levels were observed after CSLE was given orally for 50 days. Furthermore, body mass index of a CSLE dose of 50 mg/kgbw, 100 mg/kgbw and orlistat (120 mg/kgbw) group are 0.68, 0.57 and 0.52, respectively. The total body weight of the CLSE dose of 100 mg/kgbw group showed the lowest percentage change, followed by a CLSE dose of 50 mg/kgbw compared to the normal and positive control group. The carcass fat index of CSLE dose of 100 mg/kgbw was not significantly different from orlistat, which was in line with its total cholesterol level and triglyceride (p < 0.05). The binding affinity of selected compounds from Calophyllum soulattri (friedelin, caloxanthone B, macluraxanthone, stigmasterol, trapezifolixanthone, dombakinaxanthone, and brasixanthone B) to FTO are -8.27, -9.74, -8.48, -9.34, -8.85, -8.68 and -9.39 kcal/mol, which are better than that of orlistat at -4.80 kcal/mol. The molecular dynamics simulation showed that the interaction between Caloxanthone B compounds and obesity receptors was relatively stable. Lipinski's rule determined the absorption percentage of all compounds above 90% with good drug-likeness. The results showed the potential of CSLE as an antiobesity drug candidate.